Attitudes to migration and the market for news - Razi Farukh; Matthias Heinz; Anna Kerkhof; Heiner Schumacher (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
Do news outlets push overly positive or negative attitudes to migration in their coverage, or do they try to maintain a neutral and holistic perspective on the topic? To study media slant in the context of migration, we collect and code migration-related pictures that news outlets publish and - to establish a benchmark - compare them to the pictures that proand anti-migration ideological campaigns use in promotion materials. We find that most national news outlets in Germany adopt an attitude to migration that is closer to pro- than to anti-migration campaigns. All news outlets except one tabloid newspaper maintain their attitude to migration even when consumers become more critical of migration over time. Moreover, all news outlets use pictures with very diverse evaluations. Their position on migration largely follows their political orientation. We also use our method to compare the media slant in the context of migration between Germany, Hungary, and the US.
Keywords: D83; L82; O15; 330; News Markets; Media Slant; Polarization